Water absorption properties of graphene nanoplatelets filled bamboo/kenaf reinforced polylactic acid hybrid composites - Azka, Muhammad Adlan; Salit, M. Sapuan; Zainudin, E. S. (Elsevier B.V., 2025)
Environmental issues have resulted in the forming of sustainable materials, including natural fiber-reinforced PLA composites; nonetheless, this composite has low water resistance, resulting in poor composite performance. This research aims to investigate the impact of adding a small amount of graphene nanoplatelets (GNP) on the water absorption (WA) characteristic of bamboo/kenaf-reinforced PLA hybrid composites. The physical behavior and water resistance of the composites, as well as the mechanical performance and surface after 14 days of immersion, were comprehensively investigated. The study discovered that adding a small amount of GNP to composites increased their density, with the highest density of 1.6326 g/cm3 (1GBK), and altered the chemical composition's transmittance. Also, the inclusion of GNP increases the composite's crystallinity. Furthermore, the addition of GNP resulted in a decline in WA, with the lowest absorption being 4.95 % (1GBK), which is supported by the composites' increased contact angle. After 14 days of immersion, the GNP-filled composites were superior to the BK sample in terms of mechanical properties. When fibers absorb water, their surface degrades because the fibers are swelling, but GNP functions as a water barrier, preventing surface degradation due to inhibition of fiber swelling. This study highlights the potential for a straightforward and economical method to address the limited water resistance of bamboo/kenaf-reinforced PLA hybrid composites, a limitation that hinders their widespread use.